Formulation and characterization of spray-dried clarithromycin microparticles with improved dissolution and potential for oral bioavailability - Sagar Kamble; Ajay Salvi; Shivaji Patil; Yogesh Borhade (Creative Pharma Assent, 2026)
Background: Clarithromycin, a macrolide antibiotic, exhibits limited aqueous solubility, which restricts its dissolution and bioavailability. Enhancing its solubility through novel formulation strategies is essential to improve therapeutic efficacy. Spray drying with hydrophilic carriers is an effective approach for drug particle engineering to improve dissolution. Methodology: Clarithromycin microparticles were prepared by the spray drying technique using hydroxypropyl-β-cyclodextrin (HP-β-CD) and Kollicoat IR® as hydrophilic polymers. The formulations were prepared in different drug-to-polymer ratios. Physicochemical characterization was performed using differential scanning calorimetry (DSC) and powder X-ray diffractometry (XRD) to study the crystalline-to-amorphous transition. Scanning electron microscopy (SEM) was used to assess particle morphology. Dissolution studies were carried out and compared with the pure drug, physical mixtures, and marketed clarithromycin tablets. Results and Discussion: DSC and XRD analyses confirmed the transformation of clarithromycin from a crystalline to an amorphous state within the spray-dried microparticles. SEM images revealed uniform spherical particles with porous surfaces. The optimized spray-dried formulation (CH 1:1) achieved 85.42 ± 0.47% drug release within 10 min and 96.28 ± 1.13% at 60 min, compared to 57.54 ± 1.54% and 81.54 ± 1.87%, respectively, for the marketed tablet. This corresponds to an approximately 1.5-fold enhancement in early dissolution. Conclusion: Spray drying with HP-β-CD and Kollicoat IR® successfully enhanced the solubility and dissolution of clarithromycin. The approach demonstrates potential to develop effective immediate-release tablets, with markedly improved in-vitro dissolution compared with the marketed product, indicating potential for enhanced oral bioavailability.